Toward robust early-warning models: A horse race, ensembles and model uncertainty - Markus Holopainen; Peter Sarlin (Bank of Finland, 2015)
This paper presents first steps toward robust early-warning models. We conduct a horse race of conventional statistical methods and more recent machine learning methods. As early-warning models based upon one approach are oftentimes built in isolation of other methods, the exercise is of high relevance for assessing the relative performance of a wide variety of methods. Further, we test various ensemble approaches to aggregating the information products of the built early-warning models, providing a more robust basis for measuring country-level vulnerabilities. Finally, we provide approaches to estimating model uncertainty in early-warning exercises, particularly model performance uncertainty and model output uncertainty. The approaches put forward in this paper are shown with Europe as a playground.
URN:NBN:fi:bof-201503041097
Keywords: E44; F30; G01; G15; C43; 330